2020
DOI: 10.1007/s40670-020-01170-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound as a Learning Tool in Bachelor-Level Anatomy Education

Abstract: Point of care ultrasound (POCUS) has become an increasingly common diagnostic tool in the clinical environment. As a result, it is being used earlier for medical students in Undergraduate Medical Education (UME) as a learning tool for the basic sciences including gross anatomy. There is little literature, however, to support its utility for basic science education in students currently seeking a bachelor's degree. This study consisted of fourteen currently enrolled bachelor students with previous instruction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…These finding were supported by a recent study demonstrating a statistically significant improvement in test scores in the ultrasound group following a simulation versus didactic teaching session (Shah et al, 2019). Alexander et al (2021) found that ultrasound was a useful educational tool when teaching anatomy to non-medical students as well. Kondrashov et al (2015) found that students who undertook a clinical ultrasound elective course had significant improvement in their post-test anatomy exam score in comparison to their pre-test.…”
Section: Introductionsupporting
confidence: 55%
“…These finding were supported by a recent study demonstrating a statistically significant improvement in test scores in the ultrasound group following a simulation versus didactic teaching session (Shah et al, 2019). Alexander et al (2021) found that ultrasound was a useful educational tool when teaching anatomy to non-medical students as well. Kondrashov et al (2015) found that students who undertook a clinical ultrasound elective course had significant improvement in their post-test anatomy exam score in comparison to their pre-test.…”
Section: Introductionsupporting
confidence: 55%
“…This result may be due to the vast difference between ultrasound images and the actual appearance of gross anatomy in the cadaver. Generally, ultrasound helps students learn the location and relationships between anatomical structures and their disposition in a living human body, strengthening their cognition and concepts of anatomy [ 15 ]. Additionally, medical students can observe dynamic changes in the heart and the blood flow of vessels through ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of faculty expertise will likely remain a prominent barrier until program leaders recognize the value of and prioritize POCUS education for faculty members who lack POCUS training. Although curricular burden is an identified barrier, emerging evidence suggests that POCUS education can enhance current medical education curricula, specifically enhancing anatomy, physiology, physical examination, or other clinical skill education 43,44. This value must be weighed by educators who often face time, fiscal, and expertise constraints when building curricula.…”
Section: Discussionmentioning
confidence: 99%
“…Although curricular burden is an identifi ed barrier, emerging evidence suggests that POCUS education can enhance current medical education curricula, specifi cally enhancing anatomy, physiology, physical examination, or other clinical skill education. 43,44 This value must be weighed by educators who often face time, fi scal, and expertise constraints when building curricula. Growing evidence suggests that innovative integration methods such as student interest groups and asynchronous education can mitigate this burden, and intelligent integration can enhance rather than detract from existing curricula.…”
Section: Discussionmentioning
confidence: 99%